Ovarian Cancer: The Fallopian Tube as the Site of Origin and Opportunities for Prevention - George, Sophia H. L.; Garcia, Ruslan; Slomovitz, Brian M. (Frontiers in Oncology, 2016)
High-grade serous carcinoma is the most common and aggressive histotype of epithelial ovarian cancer, and it is the predominant histotype associated with hereditary breast and ovarian cancer syndrome (HBOC). Mutations in BRCA1 and BRCA2 are responsible for most of the known causes of HBOC, while mutations in mismatch repair genes and several genes of moderate penetrance are responsible for the remaining known hereditary risk. Women with a history of familial ovarian cancer or with known germline mutations in highly penetrant genes are offered the option risk-reducing surgery, which involves the removal of the ovaries and fallopian tubes (salpingo-oophorectomy). Growing evidence now supports the fallopian tube epithelia as an etiological site for the development of HGSC and consequently, salpingectomy alone is emerging as a prophylactic option. This review discusses the site of origin of epithelial ovarian cancer, the rationale for risk-reducing salpingectomy in the high-risk population and opportunities for salpingectomy in the low-risk population.